1992
DOI: 10.1143/jjap.31.471
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Rapid Phase Transformations in Amorphous GeTe Induced by Nanosecond Laser Pulses

Abstract: We have studied laser-induced rapid transformations of GeTe from an amorphous phase to a crystalline phase by means of nanosecond time-resolved optical reflectivity and transmission measurements. Two different processes for crystallization were observed. One of the crystallization processes is that inhomogeneous melting occurs in a laser-heated volume and large grains of crystalline GeTe are formed in the amorphous matrix. The other crystallization occurs at laser fluences well above the melting threshold. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Although the pseudobinary GeTe-SbTe alloy (and especially the Ge 2 Sb 2 Te 5 composition) is the best known candidate for PCMs, 16 both of its binary constituents, i.e., GeTe and Sb 2 Te 3 , have also demonstrated potential for phase change recording. 17,18 GeTe in particular has received increasing industrial interest as an active material in electrical PCMs, especially in nonvolatile memory devices. 19 Recently, Raoux et al 20 reported an extensive study on crystallization times in GeTe films produced via rf sputtering as a function of alloy composition.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pseudobinary GeTe-SbTe alloy (and especially the Ge 2 Sb 2 Te 5 composition) is the best known candidate for PCMs, 16 both of its binary constituents, i.e., GeTe and Sb 2 Te 3 , have also demonstrated potential for phase change recording. 17,18 GeTe in particular has received increasing industrial interest as an active material in electrical PCMs, especially in nonvolatile memory devices. 19 Recently, Raoux et al 20 reported an extensive study on crystallization times in GeTe films produced via rf sputtering as a function of alloy composition.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Computer simulations have also been proposed to calculate the time dependence of the temperature distribution, 11 and to analyze the overwrite process for phase-change media. 12,13 In these simulations, 12,13 however, the nucleation and growth processes were not distinguished and crystallization was characterized by a single timescale.…”
Section: Introductionmentioning
confidence: 99%
“…To capture the dynamic reflectance of this structure during GST phase transition, we have incorporated standard kinetics theory in our simulation [78][79][80]. The amorphization is accomplished with a very short laser pulse and the modulator is turned OFF as soon as the GST layer melts, because molten GST has same optical properties as a-GST [79,81]. However, crystal formation in amorphous GST during turning the modulator ON is a bit slower process which acts as a speed-limiting factor [82].…”
Section: B Opto-thermal Analysis Of the Modulator: Phase Transition O...mentioning
confidence: 99%